Authoritarian leadership and nurse presenteeism: the role of workload and leader identification - Geyan Shan; Wei Wang; Shengnan Wang; Yongjun Zhang; Shujie Guo; Yongxin Li (BMC, 2022)
Abstract Background Nurses' health in the workplace is crucial for ensuring the quality of healthcare. However, presenteeism, the behavior of working in a state of ill health, is widespread in the nursing industry. Considering that the origin of authoritarian leadership and the prevalence of presenteeism are inseparable from Chinese workplace culture, this study aimed to explore the impact and mechanism of authoritarian leadership on presenteeism. Methods A total of 528 nurses were recruited from four grade III level A hospitals in the present survey, which was distributed across 98 nursing teams. Participants were required to complete self-report measures on authoritarian leadership, presenteeism, workload, and leader identification. Description, correlation, and multilevel linear regressions were applied for data analysis. Results The present study found that presenteeism was significantly related to participants' demographic characteristics, such as marital status, educational level, technological title, and general health. There was a positive relationship between authoritarian leadership and presenteeism, and workload acted as a mediator in authoritarian leadership and presenteeism. Furthermore, leader identification moderated the relationship between authoritarian leadership and workload. When nurses were under high leader identification, the positive impact of authoritarian leadership on workload was reinforced. Conclusions This study revealed the potential antecedents and mechanisms of nurse presenteeism from the perspective of workplace culture. Results indicated that the excessive authoritarianism of leaders and the heavy workload faced by nurses may be the significant triggers for nurses' presenteeism. The role of leader identification is not always protective, which may heighten the relationship between dark leadership and its outcomes. These observations contribute to enriching research on presenteeism and authoritarian leadership, and provide valuable insights for cultivating healthy working behaviors.